Dessin, Design, Projet Représenter et reconfigurer les espaces ouverts - De Marco, Rosa; Poulot, Monique (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2023)
The contributions gathered in this book are from the eponymous international symposium held in Paris in 2019. They discuss the relationship that drawing, design and the project, understood here as a triad, have with the transformation of places. Drawing on a range of disciplines - architecture, urban planning, landscape design, geography and the visual arts - the authors explore the practices and tools adopted in the processes of representing and reconfiguring open spaces, and in the development of spatial projects for newly emerging territories. More specifically, the authors examine the role and future of drawing and non-discursive representation in contemporary socio-spatial transition processes.